Black swan : The force of the unpredictable in modern society - Berko, Iuliia (2021)
The purpose of this study was to find similarities and contrasts between two sets of principles formulated by Taleb and Collins with Hansen. In part one, set number one was formed from Taleb's work about Black Swan. In part two, set number two was constructed from the results of Collins' and Hansen's study. Both approaches were based on the assumption of Black Swan occurrence. Comparative analysis of two sets was made in the third part. Results showed both resemblances between the two approaches and some discrepancies. The study also showed that some of these resembled principles had been already implemented by some corporations, as Black Swan events occur more often and they want to be forearmed, while other principles were at the stage of finding ways of how they can be applied.